Teaching English Through Movies: Theoretical and Pedagogical Aspects - Yuliia Hlavatska (Pedagogical Discourse, 2024)
Some theoretical and pedagogical aspects of teaching English through movies are highlighted in the present paper. Its topicality is related to the overall aim set by any foreign language teacher: students’ motivation, their being interested in the educational process and development of communication skills. The basic goal of the article is to point up the most prominent pedagogical strategies the foreign teachers use in language classrooms to activate students in their developing language skills. The subject of the paper is English movies as the pedagogical tool of making a communication process ongoing, firstly, and embracing four language skills (listening, speaking, reading, and writing), finally. The objective and the subject of the article are deeply tied with the outlining the connection of movies with the development of students’ four language modalities; showing the relationship between movies and culture; describing the challenges in using English films in classes; illustrating numerous strategies foreign educators use. Five fruitful strategies (attracting attention, authentic, perceptive, linguistic, and confidential) have been revealed due to linguistic, pragmatic, discourse, socio-cultural and world competence. It is summarized that attracting attention strategy is deeply linked with the challenges both teachers and students deal with. Authentic strategy is associated with several didactic tasks at once (within the framework of competency-based approach). It has been found out the perceptive strategy is identified with teachers’ intentions and objectives they set, on the one hand, and students and teachers’ comprehension of movies being implemented in the educational process to develop language skills, on the other hand. The linguistic strategy is bound with the various grammatical topics which can be presented in English classes with the help of movies. The confidential strategy implies the use of productive and constructive methods to raise students’ confidence in learning English, the audio-visual approach is being noticeable.